Pengembangan Job Sheet Praktik Plambing di Pendidikan Teknik Bangunan Fakultas Teknik Universitas Negeri Jakarta sesuai dengan Standar Kompetensi Kerja Nasional Indonesia (SKKNI) - MOCHAMAD AGUNG PRASETYO SUKANTO; R. EKA MURTINUGRAHA; RIYAN ARTHUR (Risenologi, 2021)
This study aims to develop a performance assessment instrument in the form of a plumbing practice job sheet in the S1 Building Construction Education Study Program in accordance with the Indonesian National Work Competency Standards (SKKNI). This study uses the Research and Development (R&D) method with the model used, namely the 4D development model (Define, Design, Development, Disseminate). This research was conducted with a product feasibility validation test involving experts in 2 aspects, namely the material aspect and the evaluation aspect. The results of the percentage of product feasibility validation on the material aspect of 86.42% can be categorized as very feasible, while the results of product feasibility validation on the evaluation aspect get a percentage of 91,67% can be categorized as very feasible. So that the job sheet can be used in plumbing practice learning activities in the workshop to improve work competencies covering aspects of knowledge, skills and work attitudes.